SOLIDARITAS KELOMPOK MINORITAS DALAM MASYARAKAT (Studi Kasus Kelompok Waria Di Pondok Pesantren Waria Al Fatah Yogyakarta) - Munifah, Siti (Jurnal Sosiologi Agama, 2018)
In a society, based on the size of the members there are two social groups namely the majority and minority groups. Majority groups are the largest part of a society. In contrast, minority groups are the smallest part of a society. In everyday life, minority groups do not often get their rights like majority groups in general. To obtain these rights, minority social groups often form a group or community to achieve desired goals. With strong Solidarity within a group, together they (minority groups) can fight for their rights and face an external threat (conflict). Through this article, the author will give an idea how solidarity of a minority group (waria) in facing conflict especially transvestites that exist in the boarding school of Islamic transvestites Fatah Yogyakarta. Keywords: solidarity, minority, transgender, transvestite pesantren.